Pengembangan Masyarakat Melalui Kelompok Sadar Wisata (Pokdarwis) di Wisata Air Terjun Lider - Indriana, Ratih; Prayitno, Hadi (Electronical Journal of Social and Political Sciences (E-SOSPOL), 2021)
Social change makes people have knowledge in terms of tourism management. The change is made by Kelompok Sadar Wisata (Pokdarwis). This group is formed both a booster in growing community participation and as an effort in improving community welfare through Lider waterfall management activity. The research problem was how the community development carried out by Pokdarwis in Lider waterfall as the local tourism. Therefore, this research was aimed to find out and describe the community development process carried out by Pokdarwis. This descriptive research employed a qualitative approach. The research informants were determined by using purposive technique. The research data were collected through non-participant observation, interviews and documentation. Then, the data were analyzed by using data collection, data reduction, data display and verification. To test data validity, researchers used source triangulation technique. The findings indicated that the community development conducted by Pokdarwis was able to increase the economy of the community, to increase social relations, and to grow community participation. Furthermore, there were two existing programs carried out by Pokdarwis, namely increasing human resources and increasing creativity and innovation